Expectations structure in asset pricing experiments - Giulio Bottazzi; Giovanna Devetag (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
Notwithstanding the recognized importance of traders' expectations in characterizing the observed market dynamics, for instance the formation of speculative bubbles and crashes on financial markets, little attention has been devoted so far by economists to a rigorous study of expectation formation in the laboratory. In this work we describe a laboratory experiment on the emergence and coordination of expectations in a pure exchange framework. We largely base our study on previous experiments on expectation formation in a controlled laboratory environment by Cars Hommes, Joep Sonnemans, Ian Tuinstra and Henk van de Velden (2002a). We consider a simple two asset economy with a riskless bond and a risky stock. Each market is composed of six experimental subjects who act as financial advisors of myopic risk-averse utility maximizing investors and are rewarded according to how well their forecasts perform in the market. The participants are asked to predict not only the price of the risky asset at time t+1, as in Hommes et al. (2002a), but also the confidence interval of their prediction, knowing the past realizations of the price until time t-1. The realized asset price is derived from a Walrasian market equilibrium equation, unknown to the subjects, with feedback from individual forecasts. Subjects' earnings are proportional to the increase in their wealth level. With respect to previous experiments that did not include an explicit evaluation of risk by participants, we observe a higher price volatility, a decreased likelihood of bubble dynamics and, in general, a higher heterogeneity of predictions.
Keywords: C91; C92; D84; G12; G14; 330; experimental economics; expectations; coordination; asset pricing; Erwartungstheorie; CAPM; Test